Revitalization of Religious Understanding among Elementary School Students at An-Nur Mosque Bengkulu City - Mus Mulyad; Agusman Rahim; Intan Risky Anggraeni; Verlia Sari; Melza Zartika (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aimed to analyze the revitalization of religious understanding among elementary school students through TPQ activities at An-Nur Mosque, Padang Tekurung IV, Betungan Subdistrict, Bengkulu City. This study employed a qualitative descriptive research design to examine the implementation of religious educational activities conducted within the mosque environment. Research participants consisted of mosque administrators, TPQ teachers, parents, and elementary school students involved in TPQ activities. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicated that TPQ activities contributed positively to strengthening students’ religious understanding through Qur’an reading instruction, worship practices, and moral education activities. Educational programs implemented through TPQ also increased students’ participation, learning enthusiasm, and religious awareness. Positive changes were observed in students’ discipline, responsibility, and religious behavior during learning activities. Support from teachers, parents, and community members played an important role in maintaining the continuity and effectiveness of the educational programs. The study concludes that mosque-based educational activities can become effective strategies for strengthening religious understanding and developing religious character among elementary school students.